PENERAPAN METODE WAHDAH SEBAGAI UPAYA MENINGKATKAN TAHFIDZUL QURAN SISWA - Arga Wulang Loh Sandi; Arip Febrianto (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2020)
This study aims to determine the Implementation of the 8 Juz of Tahfidzul Quran at SDIT Salsabila 4 Jetis Bantul. This research is qualitative. The subjects of this study were the principal and the Tahfidz teachers. Data collection techniques were interviews, observation, and documentation. The data analysis technique used was descriptive qualitative. I was checking the validity of the data used technical triangulation and source triangulation. The results of the study showed that the implementation of the 8 Juz of  Tahfidzul Quran Method in SDIT Salsabila 4 Jetis could reach the target using the wahdah method. And the rules in memorizing the Quran, really implemented. Of eighteen Tahfidzul Quran students, nine students meet the 8 Juz target.Keywords: Wahdah Methods, Tahfidzul Quran, 8 Juz